Analisis Produktivitas Grinding Ball Menggunakan Metode Objective Matrix Dan Fault Tree Analysis - Henri Junianto Naibaho; Andung Jati Nugroho (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
Instability in the production of CV Barokah Logam Sejahtera's grinding balls still occurs frequently. In 2022, production is unstable because every month there is a huge difference in production results. In February 2022, CV Barokah Logam Sejahtera experienced an increase in production by 10,000 kg. In April 2022, CV Barokah Logam Sejahtera experienced a decrease in production by 10,000 kg. The purpose of this final project research is to find out the productivity of the production department at CV Barokah Logam Sejahtera during the period January 2022 to December 2022, to find out the causes (basic events) of the instability of grinding ball production at CV Barokah Logam Sejahtera during the period January 2022 to December 2022 and to determine proposed improvements to the basic event of grinding ball production instability at CV Barokah Logam Sejahtera. The methods used in data processing are Objective Matrix and Fault Tree Analysis. The results of this study are for the highest productivity value to occur in August 2022 with a value of 853 with 3 criteria being at a level above the average. Meanwhile, the lowest value occurred in July 2022 with a value of 159. The highest decrease in productivity occurred in October 2022 with a productivity value of 178, down from September 2022 with a productivity value of 746. The cause of the instability of grinding ball production at CV Barokah Logam Sejahtera is Incorrect Raw Material Purchases Time, Raw Material Usage Exceeds Usage Limit, Product Demand Exceeds Production Capacity, there is dirt in the molten metal, there is air in the mold, the mold temperature is not appropriate (not quite right), the cooling water is too hot, the molten metal is not fully poured, the molten metal temperature is not normal, and the molten metal has been poured too much. Proposed improvements to the basic event of grinding ball production instability at CV Barokah Logam Sejahtera are to make a raw material purchase plan based on the EOQ method, purchase raw materials according to the raw material purchase plan obtained.